Social acceptance by senior citizens and caregivers of a fall detection system using range sensors in a nursing home. (1st February 2016) - Iio, Takamasa; Shiomi, Masahiro; Kamei, Koji; Sharma, Chandraprakash; Hagita, Norihiro
Abstract: We developed a fall detection system with a status view function using range sensors in nursing homes and investigated how it was evaluated by seniors and caregivers about their intention to use and feelings of security. Our system calculates the positions and heights of seniors using range sensors for falling detection and sends an alert to the terminals of caregivers. Moreover, the system sends silhouette images from the range sensors that display the largest appearance of a person to the terminal to provide detailed information of seniors for the caregivers. In user evaluation, seniors and caregivers watched the three videos: simulated out-of-bed sensor, fall detection under constant observation and fall detection without constant observation. Participants answered questionnaires and were interviewed after watching each video. As a result, the seniors indicated significantly higher intention to use and feelings of security in the second and third videos than in the first video. Most seniors could accept being constantly monitored by the caregivers because they deemed safety to be more important than privacy. A few seniors (often healthy individuals) felt nervous under constant observation. Caregivers commented on the importance of flexibly switching the functions of the fall detection system to reflect individual status. Abstract :